A DES Procedure Applied to a Wall-Mounted Hump. (28th August 2012) - Bozinoski, Radoslav; Davis, Roger L.
Abstract : This paper describes a detached-eddy simulation (DES) for the flow over a wall-mounted hump. The Reynolds number based on the hump chord is Re c = 9.36 × 10 5 with an in-let Mach number of 0.1. Solutions of the three-dimensional Reynolds-averaged Navier-Stokes (RANS) procedure are obtained using the Wilcox k − ω equations. The DES results are obtained using the model presented by Bush and Mani and are compared with RANS solutions and experimental data from NASA's 2004 Computational Fluid Dynamics Validation on Synthetic Jets and Turbulent Separation Control Workshop. The DES procedure exhibited a three-dimensional flow structure in the wake, with a 13.65% shorter mean separation region compared to RANS and a mean reattachment length that is in good agreement with experimental measurements. DES predictions of the pressure coefficient in the separation region also exhibit good agreement with experiment and are more accurate than RANS predictions.